Agri vs. food? Perceptions of local policymakers on agri-food policies from a multilevel approach - López-García, Daniel; Cruz-Maceín, Jose Luis; DiPaula, Martina (Frontiers in Sustainable Food Systems, 2024)
In order to understand multi-level configurations of agro-food policies to promote Sustainable Food Systems (SFS), this paper strives to identify the challenges that municipal policymakers face, from a multi-level governance perspective. To this end, we have studied the policies implemented in 10 different municipalities of the Madrid Region (Spain) through in-depth interviews and secondary documentation analysis are studied and the challenges these municipalities are facing are analysed from a multi-scale and territorialised perspective. The following research objectives are addressed: (1) description of the type of policies implemented for the promotion of SFS and the narrative frameworks in which they are shaped; (2) identification of challenges of local policies to support SFS especially governance challenges; and (3) proposals for the promotion of sustainable food systems through a multi-level, territorialised governance perspective. The paper identifies three main axes of tension and discoordination -municipal Vs regional powers; agricultural Vs food policies; and rural Vs urban territories -that constrains the sustainability potential of multi-level agro food policies. Finally we provide a comprehensive, sustainable scheme to assess local agro-food governance throughout a multi-level and multi-actor approach, setting interrelations between the different levels, actors and agencies involved to overcome the lock-ins identified.